O processo de nucleação escolar no campo: implicações na educação infantil das crianças do campo no Município de Limoeiro- PE - Soares, Maria do Carmo de Moura Silva (2017)
In a scenario of hegemonic globalization driven by the forces of neoliberal capitalism, the policies of structural adjustment and macroeconomic stabilization undertaken in peripheral and semi-peripheral national states, provoke turmoil in legal frameworks and institutional arrangements, causing erosion of the social contract and the grave retreat from social citizenship. This is reflected in the social injustices suffered by those who live and / or work in the Brazilian countryside and who suffer the expropriation of land, the means of production of life, the territories and spaces of reproduction of their collective cultural identities. For Santos (2005, 2008, 2016), there is a favorable environment for the configuration of social fascism, which is reflected in the worsening of social exclusion and the deepening of social inequalities. Contemporary social policy, stemming from neoliberal reforms, is based on the model of public management, whose main focus is effectiveness, acting with its strategies, instruments and control mechanisms, aiming at quality / performance. In this context, one can identify the formation and consolidation of some forms of sociability built on the basis of individualism and the competitiveness of hegemonic neoliberal capitalism, manifested in the implementation of policies, societal processes and social relations that are constructed in the local context, in the daily life of communities and schools. The present research aims to investigate the societal processes and modes of sociability present in the implementation of school nucleation policy in the field adopted in the municipality of Limoeiro - PE and its implications in Early Childhood Education. This is an exploratory field research with a qualitative approach. As a methodological resource, the in-depth interview was used, which, according to Duarte (2006), enables the researcher to search for and collect answers from subjective experiences. As a result, the thesis was confirmed that the policy of school nucleation in the field, adopted by the municipality of Limoeiro - PE, was implemented within the sociabilities investigated in this research from the following: insecurity, accountability, monoculturalism and conformism. These sociabilities, articulated with certain social processes, contribute to the demobilization of the subjects and to the weakening of the resistance to the effects of hegemonic globalization. A community that has little articulation with the social movements of the countryside is a fertile ground for the establishment of exclusive hegemonic societal processes. School nucleation presents itself as an obstacle for the Infantile Education of the Field to reach schools in the rural context and constitute counter-hegemonic spaces. It remains the monocultural educational project antecedent to school nucleation, deprived of the conception of Field Education and conducive to the manufacture of non-existence of these subjects as subjects of culture and law. On the other hand, the outbreaks of indignation are identified as spaces of hope for the rupture of conformism and for the empowerment of other sociabilities committed to the construction of a subaltern and insurgent cosmopolitanism through the organization of local networks articulated with other national and transnational networks, in order to strengthen the resistance and the memory of the peoples of the countryside, seeking their full citizenship.